2020
DOI: 10.1093/europace/euz346
|View full text |Cite|
|
Sign up to set email alerts
|

The influence of scar on the spatio-temporal relationship between electrical and mechanical activation in heart failure patients

Abstract: Aims The aim of this study was to determine the relationship between electrical and mechanical activation in heart failure (HF) patients and whether electromechanical coupling is affected by scar. Methods and results Seventy HF patients referred for cardiac resynchronization therapy or biological therapy underwent endocardial anatomo-electromechanical mapping (AEMM) and delayed-enhancement magnetic resonance (CMR) scans. Area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…As of many comparisons in this study, we found an internal heavier burden in the midseptal region of Group B, which is also the region in which the mechanical activation front splits in two, lingering before activating the neighboring apical and anterolateral regions. Maffesanti et al showed, with a similar setup to the one presented here, how a significant scar burden can significantly alter electromechanical synchronization and activation centroids 28 . This is accordance with our findings, although we could not distinguish between significant and non-significant scar burden, due to small sample size.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…As of many comparisons in this study, we found an internal heavier burden in the midseptal region of Group B, which is also the region in which the mechanical activation front splits in two, lingering before activating the neighboring apical and anterolateral regions. Maffesanti et al showed, with a similar setup to the one presented here, how a significant scar burden can significantly alter electromechanical synchronization and activation centroids 28 . This is accordance with our findings, although we could not distinguish between significant and non-significant scar burden, due to small sample size.…”
Section: Discussionmentioning
confidence: 64%
“…Importantly, ischemic HFrEF with concomitant LBBB may result in remodeling of ventricular EM coupling and geometry, disrupting LV mechanical activity and rotation pattern [25][26][27] . Remarkably, these changes can affect myocardium proximal to the ischemic region, as well as the remote one 28 . Similarly to our findings, Paoletti Perini et al 4 demonstrated, that, in patient with HF and co-existing LBBB, reduction of LV apex-basal rotation and www.nature.com/scientificreports/ global twist was associated with segmental rotational dyssynchrony.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Importantly, the extent of electromechanical uncoupling is variable and dependent on electrical and nonelectrical substrates, including regional hypocontractility and myocardial scar (Figure 2). 7,14 Here, lack of coupling implies electrical depolarization of a cardiac segment without synchronous myocardial fiber shortening. Due to uncoupling, however, sites of latest mechanical activation occur more frequently in a nonlaterally located segment than electrical activation, which complicates selection of optimal transvenous LVLP.…”
Section: Challenge Of Electromechanical Dissociationmentioning
confidence: 99%
“…Due to uncoupling, however, sites of latest mechanical activation occur more frequently in a nonlaterally located segment than electrical activation, which complicates selection of optimal transvenous LVLP. 14 Based on our understanding of conduction disorders that cause dyssynchrony, 2 distinct approaches to enhance LVLP in dyssynchronous HF can be proposed (Figure 1).…”
Section: Challenge Of Electromechanical Dissociationmentioning
confidence: 99%